1998
DOI: 10.1103/physrevlett.80.4080
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Electronic Bond Breaking and Desorption of Adatoms on Si(111)-(7×7)

Abstract: Laser-induced structural changes on the Si(111)-͑7 3 7͒ surface were studied for laser fluences below thresholds of melting and ablation. The adatoms of the reconstructed structure are removed selectively by an electronic process, and Si atoms in the electronic ground state are ejected with a peak translational energy of 0.15 eV. The electronic process of this bond breaking of adatoms exhibits the site-sensitive efficiency which shows a resonant wavelength dependence and is highly superlinear with respect to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 16 publications
1
40
0
Order By: Relevance
“…These cross sections are much lower than for the excitonic mechanism on surfaces. Later work [15,16] showed that atoms are removed from surfaces of GaAs (1 1 0 [18]. The number of atoms emitted in the ground state is a superlinear function of¯uence, and agrees with that of the number of vacancies generated.…”
Section: Smoothing or Roughening The Surfacementioning
confidence: 51%
“…These cross sections are much lower than for the excitonic mechanism on surfaces. Later work [15,16] showed that atoms are removed from surfaces of GaAs (1 1 0 [18]. The number of atoms emitted in the ground state is a superlinear function of¯uence, and agrees with that of the number of vacancies generated.…”
Section: Smoothing or Roughening The Surfacementioning
confidence: 51%
“…In addition, three bonds between Si adatoms and Si restatoms in the Si(1 1 1)-(7 · 7)A:Cl surface are distorted so increased hole-hole localization at those sites increases back-bond breakage while inhibiting Cl + desorption. Similar hole localization arguments have been given to explain the laser-induced desorption of adatoms from Si(1 1 1)-(7 · 7) [1].…”
mentioning
confidence: 56%
“…To date, attempts to demonstrate site specific desorption have been restricted to laser stimulated desorption of Si adatoms from Si(1 1 1)-(7 · 7) [1], Si dimers on Si(1 0 0)-(2 · 1) [2], and P and In atoms from InP(1 1 0)-(1 · 1) [3]. Though it is well known that the electronic excitations involved in laser stimulated desorption of semiconducting and ionic materials are often the same as those governing electron stimulated desorption (ESD) [4], the success in demonstrating spatial control and site specificity in ESD is indeed limited.…”
mentioning
confidence: 99%
“…Laser-based strategies for controlled surface modification benefit from better understanding of fundamental mechanisms that convert photon energy into bond breaking and desorption from particular surface sites. Such mechanisms have been suggested for semiconductor [4] and metal surfaces [5,6] and control of velocity and electronic state distributions of halogen atoms desorbed from alkali halide surfaces, by selective laser excitation of surface excitons, has been reviewed recently [1]. However, controlled laser modification of metal oxide surfaces is a much more challenging problem due to diverse material electronic properties and geometric structures.…”
Section: Introductionmentioning
confidence: 98%